2019
DOI: 10.1177/1088767919852381
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Solved and Unsolved No-Body Homicides in Australia: An Exploratory Analysis

Abstract: Factors that are both within and outside of police discretion can pose challenges to solving homicides generally. There has been little study of no-body homicides, nor why some remain unresolved. This analysis compares solved and unsolved no-body homicides in Australia using Pearson’s chi-square tests of independence. Coroners’ findings, case law, and media reports from 1983 to 2017 were examined. Cases ( N = 55; 42.4% solved) differed based on the victim’s age, who reported them missing, reward money, Coronia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Similar findings have been observed in the literature on DA and CSS. For example, research by Ferguson and Pooley (2019a, b) revealed “no-body” cases in Australia commonly involved homicides where the victim was reported missing and deemed a low-risk of harm initially. Cases such as these were commonly unclassified as homicides for a significant period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been observed in the literature on DA and CSS. For example, research by Ferguson and Pooley (2019a, b) revealed “no-body” cases in Australia commonly involved homicides where the victim was reported missing and deemed a low-risk of harm initially. Cases such as these were commonly unclassified as homicides for a significant period.…”
Section: Discussionmentioning
confidence: 99%
“…Cases such as these were commonly unclassified as homicides for a significant period. The delays created by initial perception of the missing person as low-risk, the complexity added by the absence of a victim’s body and lies told by POIs resulted in numerous examples like the WA case, where perpetrators could not be prosecuted and the homicide remained unsolved (Ferguson and Pooley, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Some prosecutors decline progressing cases to trial without a body, placing significant importance on physical evidence in court trials (Godwin, 1998; Reale & Beauregard, 2019). The absence of a body, or limited evidence on it when found, may be due to several factors regarding the location in which it was disposed of, including the rate of decomposition, weather conditions, or submersion in water (Ferguson & Pooley, 2019). Without the identification of a body and subsequent disposal site, there are limitations for evidence collection.…”
Section: Introductionmentioning
confidence: 99%
“…Without the identification of a body and subsequent disposal site, there are limitations for evidence collection. Even if these sites are located, they may have already suffered from tampering or contamination (Ferguson, 2011; Ferguson & Pooley, 2019; Reale & Beauregard, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation